2019
DOI: 10.1061/(asce)cc.1943-5614.0000949
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impressed Current Cathodic Protection and FRCM Strengthening for Corrosion-Prone Concrete Structures

Abstract: :This study introduces the use of the combined impressed current cathodic protectionstructural strengthening (ICCP-SS) as a technique for repairing reinforced concrete (RC) structures that have been subjected to chloride-induced corrosion. The development of this technique is based on the combination of a carbon fiber mesh (CF-MESH) and a polymer-modified cementitious matrix to produce a carbon fiber reinforced cementitious matrix (C-FRCM). Firstly, the effects of different types and amounts of high molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The CFRP was used as the auxiliary electrode for measuring the current flow (∆I), which was induced by an externally imposed potential shift (∆E) of 20 mV. Thus, the polarization resistance R p and corrosion current (I corr ) can be calculated with Equations (1) and (2). The value of B is normally assumed to be 25 mV for actively corroded steel in concrete [18].…”
Section: Testing Programmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFRP was used as the auxiliary electrode for measuring the current flow (∆I), which was induced by an externally imposed potential shift (∆E) of 20 mV. Thus, the polarization resistance R p and corrosion current (I corr ) can be calculated with Equations (1) and (2). The value of B is normally assumed to be 25 mV for actively corroded steel in concrete [18].…”
Section: Testing Programmentioning
confidence: 99%
“…In recent years, a new intervention system, integrating impressed current cathodic protection (ICCP) with structural strengthening (SS), has been proposed to be ICCP-SS for improving the maintenance of concrete suffered from the corrosion of steels induced by chloride [1][2][3][4]. Structural strengthening by FRP or steel plates has been proven to be an effective method of improving the structural performance of corroded concrete structures, although the performance might degrade later due to the continuous corrosion of the steel in the concrete [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tests on columns with corroded reinforcing steel, protected by the ICCP-SS system, showed that the system worked successfully with regard to both its protecting and its strengthening function (Su et al, 2 and Zhu et al, 3,4 ) The performance of the CFRP anode was investigated in a simulated ICCP system with an electrode composed of 3% NaCl solution, NaOH solution, and simulated pore solution. On the one hand, the CFRP could operate in a stable way in all three solutions, and the electrochemical performance was not significantly compromised during 50 days of polarization when the applied current was as high as 6.15 A/m 2 .…”
Section: Researchmentioning
confidence: 99%
“…For this reason, more recently, a new type of composites was considered for the structural retrofitting: Fabric Reinforced Cementitious Mortar (FRCM) [9][10][11][12][13][14][15][16][17][18][19][20][21]. The main idea consists of substituting the resin with an inorganic-like matrix.…”
Section: Introductionmentioning
confidence: 99%